1996
DOI: 10.1016/0014-5793(96)00158-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of RII‐binding proteins in the mollusc Mytilus galloprovincialis

Abstract: Several proteins with Mr > 70 kDa from various tissues of the sea mussel Mytilus gailoprovincialis were specifically recognized in vitro by the regulatory submit (type Rllc0 of cAMP-dependent protein Idnase (cAPK) from porcine heart. However, none of these proteins interacted with the regulatory submit of cAPK from the mollusc itself. The results suggest that, unlike mammalian RII, regulatory subunit from mussel lacks the specific residues responsible for interaction with R-binding proteins. Consequently, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Furthermore, the particular localization of the R myt2 isoform suggests that it may be associated with cellular structures and organella, through its interaction with anchoring proteins, like occurs with the RII-type subunit from mammals (Pawson and Scott 1997;Michel and Scott 2002). However, our attempts to identify these PKA-anchoring proteins in mantle extracts were so far unsuccessful (Cao et al 1996). In previous work we had been reported that R myt1 and R myt2 have specific structural and biochemical properties besides its common ability to inhibit the C-subunit in the absence of cAMP.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, the particular localization of the R myt2 isoform suggests that it may be associated with cellular structures and organella, through its interaction with anchoring proteins, like occurs with the RII-type subunit from mammals (Pawson and Scott 1997;Michel and Scott 2002). However, our attempts to identify these PKA-anchoring proteins in mantle extracts were so far unsuccessful (Cao et al 1996). In previous work we had been reported that R myt1 and R myt2 have specific structural and biochemical properties besides its common ability to inhibit the C-subunit in the absence of cAMP.…”
Section: Discussionmentioning
confidence: 90%